The Existence of PAI Teachers in PAI Learning during the Covid-19 Pandemic - Devi Indah Sari; Aulia Ramadhani Lubis (Matondang Journal, 2022)
This study aims to elaborate further on the role of PAI teachers in the midst of a pandemic, the strategies used, the obstacles encountered, the efforts made and what are the challenges for PAI teachers in carrying out their duties in the midst of the Covid-19 pandemic. This study uses a type of qualitative research method. Kirk and Miller define that qualitative research is a particular tradition in the social sciences that is fundamentally dependent on observations of humans both in terms of their area and in terms. This study uses a qualitative method because the researcher considers the problem under study to be quite complex and dynamic so that the data obtained from the informants is captured by a more natural method, namely direct interviews with the informants so that natural answers are obtained. In addition, the researcher intends to understand the social situation in depth, find patterns and theories that are in accordance with the data obtained in the field.